KEWENANGAN PEMERINTAH PROVINSI BALI DALAM MENGATUR USAHA BIRO PERJALANAN WISATA - I Ketut Suparta; I Made Budiasa (Soshum: Jurnal Sosial dan Humaniora, 2013)
The study is titled "Authority of the Provincial Government of Bali in regulate a Travel Agency Business”, and is a normative legal research moved from the norm conflicts that occur between Bali Provincial Regulation No. 1 of 2010 on Travel Service Business with the Regulation of the Minister of Culture and Tourism number: PM.85/HK.501/MKP/2010 on Procedures for Travel Services Business Registration which then raises two issues, namely: Is Bali provincial government is authorized to regulate the business of a travel bureau and whether the source of the authority of the Provincial Government of Bali in regulating business bureau Travel?. In this study, the approach are statute approah and legal concept analysis approach, then the problem is analyzed with the technique later in systematizing description for further evaluated and given argumentation.From the research and discussion that is done it can be known that the provincial government of Bali has the authority to regulate the business of Travel Agents Tourism as provided for in Article 29 letters c Act Number 10 Year 2009 concerning tourism in conjunction with Article 14 paragraph (1) letters d and an explanation as its lex and Article 13 paragraph (2) of Act No. 32 Year 2004 on Regional Government as its lex generalis. Where the authority of the provincial government of Bali is attributive authority, ie the authority that comes from the act so that no new authority owned by the provincial government of Bali to arrange business travel bureau.